Penguatan Literasi Green Economy Dan Keagamaan Melalui Pengabdian Masyarakat Berbasis Al-Islam Dan Kemuhammadiyahan Di PKBM Pra 02 Bontaeng Gowa - Nadilla S; Mega Mustika; Dwi Nur Isra; Amirah Fauziah; Dhea Amelia; Windah Nur Syafitri; Andi Novianti; Nur Istiqomah; Almara Nataya Fausan; Hajratul Wahda; Nur Fadilah Ramadhani Putri; Fahriji Ulfa; Muh Irsan; Akbar Gusfiar; Futra, Futra; Muhammad Ardhan Arifin (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
Environmental crisis and limited religious knowledge in marginalized communities are significant challenges in creating sustainable development. This community service activity aims to strengthen understanding of Green Economy and Islamic values ​​through the Al-Islam and Muhammadiyah approaches at PKBM PRA 02 Bontaeng, Gowa. The method applied is a participatory qualitative approach, with stages of activity that include observation, program implementation (Green Economy workshop, training in crafts from used goods, and teaching the Koran), and evaluation. The results of this activity show an increase in participants' understanding of the Green Economy concept (from 80% who did not know to 78% who were able to explain), an increase in residents' ability to process waste into creative products, and the development of basic religious understanding in children. The practical da'wah approach has proven effective in meeting the socio-ecological needs of marginalized communities. This program reflects a holistic empowerment model and has the potential to be applied in areas with similar characteristics.